EDUKASI PERSONAL HYGIENE SEBAGAI UPAYA MENINGKATKAN PENGETAHUAN DAN KETERAMPILAN PERSONAL HYGIENE PADA ANAK USIA SEKOLAH DASAR KELAS 6 DI MI NEGERI 1 BANYUMAS - Rohmah, Afifa Tur; Wirakhmi, Ikit Netra; Safitri, Maya (Fakultas Ilmu Kesehatan Universitas Borneo Tarakan, 2025)
AbstractVarious diseases are caused by poor personal hygiene with possible infections of the skin, respiratory tract, and digestive tract organs including diarrhea (56.73%), fever with or without cough (54.81%), worms (45.19%), lice (40.38%), scabies (39.42%), toothache (9.62%). These diseases can be found for example environmental hygiene and personal hygiene. Personal hygiene problems in children take second place in health problem statistics. Health education is an experience in providing material and learning that can affect every habit, attitude and also knowledge related to the health of oneself and the community. The media used are banners, videos, and powerpoints using lecture, discussion, and demonstration methods. The output of this PkM is a community service journal. The results of Community Service Activities that have been carried out by the author know the level of knowledge of personal hygiene education in 6th grade students at MI Negeri 1 Banyumas before and after personal hygiene education. Before the majority of knowledge education was in the sufficient category 74.1%, and the number before the majority of skill education was in the sufficient category 59.3%. After personal hygiene education, the majority of the knowledge level was in the moderate category 51.9%, and the good category 76.5%, from skill education. Providing education in this PkM activity can increase the level of knowledge and skills. Keywords: Personal Hygiene, School Children, Boarding School, Education